New Silver(I) Coordination Polymers with Hetero Donor Ligands: Synthesis, Structure, Luminescence Study and Photo‐Catalytic Behavior. Issue 28 (5th October 2017) - Kulovi, Somnath; Dalbera, Subrata; Das, Somnath; Zangrando, Ennio; Puschmann, Horst; Dalai, Sudipta
Abstract: Two new Ag(I) coordination polymers, namely, [Ag2 (dmt)2 (tph)]n (1 ), [Ag2 (dmt)2 (oxalate)]n (2 ), and a discrete neutral complex [Ag2 (dmt)4 (SO4 )].2(dmt).2(H2 O) (3 ) (where dmt=2, 4‐diamino‐6‐methyl‐1, 3, 5‐triazine, ox=oxalate anion and H2 tph=terephthalic acid) were synthesized and characterized using elemental analysis, IR, UV–vis and fluorescence spectroscopy. The solid‐state structures of complexes1–3 were determined using single crystal X‐ray crystallography. Compounds1 and2 are 1D and 3D coordination polymers, respectively, with the packing reinforced by weak interactions such as H‐bonds and π‐π stacking. The most intriguing aspect of the crystal structure of3 is a pseudo hexagonal arrangement of six dmt, connected by pairs of N−H⋅⋅⋅N hydrogen bonds, around a sulfate anion. The band gap energies of the coordination polymers were determined. All the complexes were found to be photo‐catalytically active and complex1 displays the higher catalytic activity toward the photo degradation of methylene blue (MB) in water. The higher content of aromatic moieties in1 plays a significant role in effective charge separation and transport to make it the best catalyst in the series. Abstract : Three new silver(I)‐2, 4‐diamino‐6‐methyl‐1, 3, 5‐triazine coordination polymers have been synthesized by using three different anionic ligands: terepthalate, oxalate, sulfate and characterized by X‐ray single crystal structural determination. Photocatalytic activity of these polymers with respect to methylene blue (MB) organic dye displays interesting results.